Application of a medial buttress plate may prevent many treatment failures seen after fixation of vertical femoral neck fractures in young adults. Issue 5 (May 2015) - Mir, Hassan; Collinge, Cory
Abstract Femoral neck fractures in young adults with normal bone are mostly vertically oriented and may have variable amounts of comminution, which result from shearing forces during high-energy trauma. These factors play a role in the high rate of complications after this injury, including nonunion, malunion, failure of fixation, and avascular necrosis. These problems often occur together and inter-relate, for example, nonunion or malunion frequently result from fixation failure and varus collapse of the femoral head after reconstruction. The orthopaedic surgeon's goals of obtaining and maintaining anatomic reduction until bony union have been addressed by a number of surgical approaches and fixation constructs, however, complications are still common and no consensus exists on how these problematic fractures may be best treated. For optimal treatment of vertical femoral neck fractures, anatomic reduction must be achieved and fixation must be able to resist the high shear forces across the fracture with hip motion, weight-bearing, and muscle tone. Buttress plate fixation is a common method for stabilizing fractures that require resistance to shear forces and stands as one of the basic principles of fracture care. This technique has not been widely applied to this injury pattern. We propose that the concepts of modern fracture care should be applied together for vertical femoral neck fractures in young adults. Specifically, we propose that anatomic reduction and fixation of vertically oriented femoral neck fractures with the addition of a medial buttress plate to resist shearing forces will improve on the historically high rate of complications after these difficult injuries.